Using Genetic Engineering Techniques to Develop Banana Cultivars With Fusarium Wilt Resistance and Ideal Plant Architecture - Wang, Xiaoyi; Yu, Renbo; Li, Jingyang (Frontiers in Plant Science, 2021)
Bananas (Musa spp.) are an important fruit crop worldwide. The fungus Fusarium oxysporum f. sp. cubense (Foc), which causes Fusarium wilt, is widely regarded as one of the most damaging plant diseases. Fusarium wilt has previously devastated global banana production and continues to do so today. In addition, due to the current use of high-density banana plantations, desirable banana varieties with ideal plant architecture (IPA) possess high lodging resistance, optimum photosynthesis, and efficient water absorption. These properties may help to increase banana production. Genetic engineering is useful for the development of banana varieties with Foc resistance and ideal plant architecture due to the sterility of most cultivars. However, the sustained immune response brought about by genetic engineering is always accompanied by yield reductions. To resolve this problem, we should perform functional genetic studies of the Musa genome, in conjunction with genome editing experiments, to unravel the molecular mechanisms underlying the immune response and the formation of plant architecture in the banana. Further explorations of the genes associated with Foc resistance and ideal architecture might lead to the development of banana varieties with both ideal architecture and pathogen super-resistance. Such varieties will help the banana to remain a staple food worldwide.